2005
DOI: 10.1021/bi0506829
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of Salicylate Effects on the Micro- and Mesoscopic Properties of a Dipalmitoylphosphatidylcholine Bilayer

Abstract: Salicylate, an amphiphilic molecule and a popular member of non-steroidal antiinflammatory drug family, is known to affect hearing through reduction of the electromechanical coupling in the outer hair cells of the ear. This reduction of electromotility by salicylate has been widely studied but the molecular mechanism of the phenomenon is still unknown. In this study, we investigated one aspect of salicylate's action; namely, the perturbation of electrical and mechanical membrane properties by salicylate in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
66
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 90 publications
9
66
1
Order By: Relevance
“…They found that SA significantly decreased the area per head group of lipid molecules and increased the tail order of lipid bilayer. The most important is that salicylate significantly increased the electrostatic potential at the water-lipid interface and significantly affected dipole moment fluctuations of the bilayer molecules [38]. All these findings are in support of our present findings, as they can explain both the increased resistance of the voltage, these metastable single pores may become stabilized and form great pores (single ion channels) [32], thus providing a potential possibility of perpetuated diffusion of acetylsalicylic acid through the bilayer.…”
Section: Accepted M Manuscriptsupporting
confidence: 90%
See 1 more Smart Citation
“…They found that SA significantly decreased the area per head group of lipid molecules and increased the tail order of lipid bilayer. The most important is that salicylate significantly increased the electrostatic potential at the water-lipid interface and significantly affected dipole moment fluctuations of the bilayer molecules [38]. All these findings are in support of our present findings, as they can explain both the increased resistance of the voltage, these metastable single pores may become stabilized and form great pores (single ion channels) [32], thus providing a potential possibility of perpetuated diffusion of acetylsalicylic acid through the bilayer.…”
Section: Accepted M Manuscriptsupporting
confidence: 90%
“…Song et al [38] studied the salicylate effects on the dipalmitoylphosphatidylcholine bilayer by molecular dynamics. They found that SA significantly decreased the area per head group of lipid molecules and increased the tail order of lipid bilayer.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Addition of salicylate to the external medium reduces the ψ s to about −0.023(±0.009) V. This suggests that salicylate adsorbs into the membrane decreasing the intrinsic charge asymmetry of the membrane. This is reasonable as there is much evidence to show that salicylate adsorbs into surfactant [29] and lipid [30][31][32] assemblies and cell membranes [33] increasing the surface charge density of the membranes, i.e., making it more negative. Its solubility is enhanced, relative to other benzoates, because the carbonyl and hydroxy group can form an intramolecular hydrogen bond [31] which increases its hydrophobic character and helps to drive its penetration into the membrane.…”
Section: B Maxwell Stress and Electrostrictive Effects Likely Originmentioning
confidence: 64%
“…Its solubility is enhanced, relative to other benzoates, because the carbonyl and hydroxy group can form an intramolecular hydrogen bond [31] which increases its hydrophobic character and helps to drive its penetration into the membrane. Indeed, recent molecular dynamics simulations of a lipid bilayer shows that salicylate penetrates more deeply than chloride, displacing it from the water-bilayer interface [32]. This reduction in the charge asymmetry of the membrane by adsorption of salicylate was also suggested in an atomic force microscopy (AFM) study of the HEK cell [34].…”
Section: B Maxwell Stress and Electrostrictive Effects Likely Originmentioning
confidence: 80%
“…The choice of a 2 fs time step in the AL run is typical for AL membrane simulations. 19,[26][27][28][29][30][31][32][34][35][36] We are aware that the use of constraint and multistep algorithms can allow time steps of 4 21,22 and even 5 fs, 20,23 hence more than twice larger than that employed in our test. Using a 5 fs time step in the AL run would bring the CG speed-up factor down to ≈50.…”
Section: Methodsmentioning
confidence: 99%